(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: Autologous fat injection laryngoplasty is a surgical procedure for unilateral vocal fold paralysis (UVFP) to medialize the nonfunctioning vocal fold to allow for complete glottic closure and, thus, improve phonation, protect the airway and improve symptoms of aspiration and dysphagia. Objective: This study compares the pre-and postoperative voice outcomes of autologous fat injection laryngoplasty in patients with UVFP. Materials and Methods: A prospective observational study was conducted in the Department of Otolaryngology-Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, from January 2021 to June 2022, with 20 patients having UVFP. The subjects were selected based on inclusion and exclusion criteria. Diagnosis of UVFP was identified by indirect laryngoscopy (IL) and confirmed by Fiber Optic Laryngoscopy (FOL). Patients were investigated by Voice Handicap Index (VHI) scores at four-time points: (1) Day before operation (T0), (2) 3 days post injection (T1), (3) 1 month post injection (T2), and (4) 3 months post injection (T3). All the VHI information was recorded in a prefixed questionnaire to analyze and calculate the results. Results: The age of the patients ranged from 19-55 years, with a mean age of 38.8±9.93 years. Among them, 13 were female (65%), and 7 were male (35%). Male: Female ratio was 1:1.8. Most patients (55%) had thyroid surgery, and the rest were idiopathic (45%). 75% of the vocal cord are paralyzed on the left side and 25% on the right-sided. The VHI scores improved significantly from 75.85±13.04 preoperatively to 58.70±12.38 at 3 days postoperatively (P < 0.0001); 47.50±9.51 at 1 month postoperatively (P < 0.0001), and 37.35±8.50 at 3 months postoperatively (P < 0.0001). Conclusion: Autologous fat injection laryngoplasty is a simple, safe, and cost-effective temporary phonosurgical procedure for the treatment of unilateral vocal fold paralysis, thus improving acoustic and voice-related quality of life (QOL). Bangladesh J Otorhinolaryngology 2025; 31 (1) Page- 05-15